2019
DOI: 10.3390/ijms20102405
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Impairment: Information from Animal Models on the Pathogenic Mechanisms of Cognitive Deficits

Abstract: Vascular cognitive impairment (VCI) is the second most common cause of cognitive deficit after Alzheimer’s disease. Since VCI patients represent an important target population for prevention, an ongoing effort has been made to elucidate the pathogenesis of this disorder. In this review, we summarize the information from animal models on the molecular changes that occur in the brain during a cerebral vascular insult and ultimately lead to cognitive deficits in VCI. Animal models cannot effectively represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 144 publications
0
18
0
Order By: Relevance
“…Based on this and other observations, Waller et al concluded that microglial activation is a prominent feature of age-associated white matter lesions [35]. As the resident brain immune cell, microglia may be increased in number or activated by oxidative stress associated with SVD, which contributes to the pathogenesis of dementia [36]. Our finding that a high percentage of microglia in the aging brain express GPR39, and that the density of GPR39-positive cells is increased in the white matter of MCI dlPFC implicates GPR39 in the neuroinflammation underlying aging-related cognitive decline.…”
Section: Discussionmentioning
confidence: 95%
“…Based on this and other observations, Waller et al concluded that microglial activation is a prominent feature of age-associated white matter lesions [35]. As the resident brain immune cell, microglia may be increased in number or activated by oxidative stress associated with SVD, which contributes to the pathogenesis of dementia [36]. Our finding that a high percentage of microglia in the aging brain express GPR39, and that the density of GPR39-positive cells is increased in the white matter of MCI dlPFC implicates GPR39 in the neuroinflammation underlying aging-related cognitive decline.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, CCH caused by continuously reducing CBF is the common pathomechanism of VCI, which not only reduces the supply of oxygen and nutrients, but also leads to the accumulation and deposition of harmful molecules in the brain. The sustained low cerebral blood supply caused impairment of structure and function of the blood–brain barrier (BBB) and neuronal tissue loss and finally manifests as a cognitive deficit (Dichgans and Leys, 2017; Hort et al, 2019). So far, however, no effective treatments have been applied to prevent the progression of the disease, which has led to serious social burden (Kalaria, 2016; Venkat et al, 2018).…”
Section: Links Between Ferroptosis and Vcimentioning
confidence: 99%
“…Physiological aging of the healthy brain is an age-dependent biological process and consists of deterioration of structure and function [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, brain aging can be accelerated by multiple factors, due to traumatic events [ 13 , 14 ], following neurovascular conditions [ 15 , 16 , 17 ], or related to specific brain diseases, including Alzheimer’s and Parkinson’s disease. Accelerated brain aging is often related to enhanced neurodegeneration, which includes loss of neuronal cell structure and function due to (1) metabolic changes [ 18 ], (2) neuronal cell death [ 19 ] (3) decline in the neuronal network [ 20 ], (4) neuronal functional deficiency [ 21 ], (5) decline in neuronal regeneration [ 22 , 23 , 24 ], or (6) a combination of the mentioned reasons.…”
Section: Introductionmentioning
confidence: 99%